Ergonomics study of public hospital signage - Basri @ Boseri, Ahmad Qadri; Sulaiman, Ruhaizin (Trans Tech Publications, 2013)
Background: Signage provides information and direction. It is important as a medium to show direction in offices and public buildings. It is more crucial for emergency services, specifically hospitals. Incomplete information and confusion of signage are among common issues being raised by the public to hospital management. Objective: This study is carried out to determine user height preferences of Hospital Kajang’s signage and to propose an appropriate height for its future signage. Approach: Thirty five respondents (20 male and 15 female) participated in this study. They are aged between 18 to 60 years old with the mean of age at 39 years old. Their stature height and eye-level height are measured using SECA Stable Stadiometer. They are asked to give a rating using 1-10 scale on three questions to measure their preferences towards the present signage. The studied signage is also measured using standard measuring tape. The data is analyzed using SPSS. Results: It is found that 25 respondents (71.43%) agree to say that the height of signage in Hospital Kajang is too high while 10 of them (28.57%) disagree. The signage should be 10.5 cm lower from present height in order to optimize its function for both groups. The proposed signage height should be 187.5 cm from the floor. Conclusion: The present signage in Hospital Kajang requires necessary height readjustment to satisfy the majority of its staffs and visitors. The improvement is vital to ensure the signage meet the directional purpose.